Testing indicators for trend assessment of range and habitat of low-density cetacean species in the Mediterranean Sea - Arcangeli, Antonella; Atzori, Fabrizio; Azzolin, Marta; Babey, Lucy; Campana, Ilaria; Carosso, Lara; Crosti, Roberto; Garcia-Garin, Odei; Gregorietti, Martina; Orasi, Arianna; Scuderi, Alessia; Tepsich, Paola; et al. (Frontiers in Marine Science, 2023)
Conservation of cetaceans is challenging due to their large-range, highly-dynamic nature. The EU Habitats Directive (HD) reports 78% of species in ‘unknown’ conservation status, and information on low-density/elusive species such G.griseus, G.melas, Z.cavirostris is the most scattered. The FLT-Net programme has regularly collected year-round data along trans-border fixed-transects in the Mediterranean Sea since 2007. Nearly 7,500 cetacean sightings were recorded over 500,000 km of effort with 296 of less-common species. Comparing data across two HD 6-years periods (2013-2019/2008-2012), this study aimed at testing four potential indicators to assess range and habitat short-term trends of G.griseus, G.melas, Z.cavirostris: 1) change in Observed Distributional Range-ODR based on known occurrence, calculated through the Kernel smoother within the effort area; 2) change in Ecological Potential Range-EPR extent, predicted through Spatial Distribution Models; 3) Range Pattern, assessed as overlap and shift of core areas between periods; 4) changes in ODR vs EPR. Most ODR and EPR confirmed the persistence of known important sites, especially in the Western-Mediterranean. All species, however, exhibit changes in the distribution extent (contraction or expansion) and an offshore shift, possibly indicating exploitation of new areas or avoidance of more impacted ones. Results confirmed that the ODR could underestimate the real occupied range, as referring to the effort area only; it can be used to detect trends providing that the spatio-temporal effort scale is representative of species range. The EPR allows generalising species distribution outside the effort area, defining species’ Habitat and the Occupied/Potential Range proportion. To investigate range-trends, EPR needs to be adjusted based also on the Occupied/Potential Range proportion since it could be larger than the occupied range in presence of limiting factors, or smaller, if anthropogenic pressures force the species outside the ecological niche. Using complementary indicators proved valuable to evaluate the significance of changes. The concurrent analysis of more species with similar ecology was also critical to assess whether the detected changes are species-specific or representative of broader trends. The FLT-Net sampling strategy proved adequate for trend assessment in the Western-Mediterranean and Adriatic basins, while more transects are needed to characterize the Central-Mediterranean and Aegean-Levantine ecological variability.